Efektifitas Pemberian Seduhan Jahe Terhadap Mual Muntah pada Ibu Hamil Trimester I di UPTD Puskesmas Krui - Olva Ferina; Riza Faulina (Universitas Malahayati Lampung, 2024)
ABSTRACT The Lampung Provincial Health Office showed that in 2015, nausea and vomiting in pregnant women occurred in 60–80% of primigravidas and 40–60% of multigravidas. Giving ginger infusion can help reduce the frequency of nausea and vomiting because ginger is rich in natural ingredients such as gingerol, which is very beneficial for pregnant women to relieve nausea and vomiting during pregnancy. This study aims to determine the effectiveness of giving ginger infusion on levels of nausea and vomiting in first-trimester pregnant women at the UPTD of the Krui Health Center. This study used a quasi-experimental research design (quasi-experiment) with a pre-post-test approach and a control group design. The population of all pregnant women in the first trimester was 33. The sample in this study was 30 people using a daily checklist sheet for steeping ginger and a daily checklist sheet for Fe tablets. Univariate and bivariate data analysis. The results showed that the average decrease in the frequency of nausea and vomiting in pregnant women before being given ginger infusion had an average value of 9.47, and the average decrease in the frequency of nausea and vomiting in pregnant women after being given it was 6.40. In the control group, the average initial frequency of nausea and vomiting was 8.80, and the final frequency of nausea and vomiting was 7.73. There is an effect of giving ginger infusion on the decrease in the frequency of nausea and vomiting in pregnant women in the first trimester, with a p-value of 0.00. The conclusion from giving ginger steeping is that it is very useful for reducing the frequency of nausea and vomiting in pregnant women in the first trimester, and it is recommended for pregnant women to be active in seeking information and increasing their knowledge so that they know more about nausea and vomiting in pregnancy. They are advised to carry out routine pregnancy checks, consume lots of foods that contain iron, and be able to actively participate in mother's classes and activities at posyandu. As well as making ginger infusions in an effort to prevent nausea and vomiting in pregnancy. Keywords: Pregnancy, Nausea and Vomiting, Brewed Ginger ABSTRAK Dinas Kesehatan Provinsi Lampung menunjukan pada tahun 2015 Mual dan muntah pada ibu hamil terjadi pada 60- 80% primigravida dan 40- 60% terjadi pada multigravida. Pemberian seduhan jahe dapat membantu mengurangi frekuensi mual muntah karena jahe kaya akan kandungan alami seperti gingerol yang sagat bermanfaat bagi ibu hamil agar dapat meredakan gangguan mual mutah selama kehamilan. Penelitian ini bertujuan untuk mengetahui efektifitas pemberian seduhan jahe terhadap kadar mual muntah pada ibu hamil trimester I di UPTD Puskesmas Krui. Penelitian ini menggunakan rancangan penelitian eksperimen semu (Quasi Experiment) dengan pendekatan pre post test with control group design. Populasi seluruh ibu hamil trimester I sebanyak 33 orang. Sampel dalam penelitian ini berjumlah 30 orang dengan menggunakan lembar ceklist harian seduhan jahe serta lembar ceklist harian tablet Fe. Analisa data secara univariat dan bivariat. Hasil penelitian diketahui rata - rata penurunan frekuensi mual muntah pada ibu hamil sebelum diberikan seduhan jahe yang memiliki nilai rata-rata yaitu 9,47 dan rata-rata penuruna frekuensi mual muntah pada ibu hamil sesudah diberikan menjadi 6,40. Pada kelompok kontrol rata - rata frekuensimual muntah awal yaitu 8,80 dan frekuensi mual muntah akhir 7,73. Ada pengaruh dari pemberian seduhan jahe terhadap peurunan frekuesi mual muntah pada ibu hamil trimester I dengan p-value 0,00. Kesimpulan dari pemberia seduhan jahe ini sangat bermanfaat untuk menurunkan frekuensi mual muntah pada ibu hamil trimester I dan disarankan bagi ibu hamil agar aktif dalam mencari informasi serta lebih meningkatkan pengetahuan agar lebih mengetahui tentang mual muntah pada kehamilan dan disarankan untuk melakukan pemeriksaan kehamilan secara rutin serta lebih banyak mengkonsumsi makanan yang mengandung zat besi dan untuk dapat aktif mengikuti kelas ibu serta kegiatan di posyandu. Serta menjadikan seduhan jahe sebagai salah satu upaya untuk pencegahan mual muntah dalam kehamilan. Kata Kunci: Kehamilan, Mual Muntah, Seduhan Jahe